Implementation of PLC Outseal as a Controller of Ammonia Gas Circulation in Chicken Coops with HMI Modbus Monitoring - Wahyu Cakra Ningrat (Universitas Muhammadiyah Gresik, 2023)
Indonesia's population in 2022 is recorded at 275,361,267 people, significantly increasing per year which has resulted in an increase in food needs in the chicken meat sector, the high interest in chicken meat has not been accompanied by appropriate technology, this has made the quantity and quality of chicken breeders often experience crop failures the application of system technology for controlling and monitoring air quality in chicken coops based on PLC Outseal for ammonia gas is a technology used to reduce the death rate of chickens due to poisoning by ammonia gas produced from the chicken manure itself. The technology applied to chicken farms uses the Outseal PLC microcontroller as the design brain, Arduino nano as a sensor data storage communication, the MQ135 air quality detector by checking ammonia gas levels, monitoring through the HMI Modbus software on a bluetooth connection with control on a smartphone and removing dirty air by blowers. The parameter limit for the value of ammonia gas in the chicken coop is 20 – 40 ppm. The test result that the value of the ammonia gas content in the farm is above the specified value, the condition of the cage is excess ammonia gas and the automatic actuator functions to remove ammonia gas until the ammonia gas level value returns to normal.